2020
DOI: 10.1016/j.cell.2020.08.023
|View full text |Cite
|
Sign up to set email alerts
|

The Hantavirus Surface Glycoprotein Lattice and Its Fusion Control Mechanism

Abstract: Hantaviruses are rodent-borne viruses causing serious zoonotic outbreaks worldwide for which no treatment is available. The hantavirus particles are pleomorphic and display a characteristic square surface lattice. The envelope glycoproteins Gn and Gc form heterodimers that further associate into tetrameric spikes, the lattice building blocks. The glycoproteins, which are the sole targets of neutralizing antibodies, drive virus entry via receptor-mediated endocytosis and endosomal membrane fusion. Here we descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
123
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(144 citation statements)
references
References 82 publications
8
123
0
Order By: Relevance
“…PUUV Gc Gc−P-4G2 fits well within the cryo-ET reconstruction, where the crystallographically observed conformation of domain III accurately matches a feature of the glycoprotein spike ( Figure 5C ), further supporting that PUUV Gc has crystallized in the pre-fusion conformation presented on the mature virion. Additionally, this fitting confirms the location of Gc in the density spanning from the membrane-distal globular lobes to the viral membrane, as we and others have proposed previously ( Li et al, 2016 ; Serris et al, 2020 ). The fitting locates domain III of the Gc adjacent to the membrane, allowing the transmembrane region of the C-terminus to be linked to the virion envelope ( Figures 5A and 2A ), and places the fusion loop from Gc domain II into membrane-distal lobe density in close contact with Gn ( Figure 5A and B ), in a manner similar to that observed for other class II fusion proteins and their cognate accessory proteins ( Halldorsson et al, 2018 ; Voss et al, 2010 ).…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…PUUV Gc Gc−P-4G2 fits well within the cryo-ET reconstruction, where the crystallographically observed conformation of domain III accurately matches a feature of the glycoprotein spike ( Figure 5C ), further supporting that PUUV Gc has crystallized in the pre-fusion conformation presented on the mature virion. Additionally, this fitting confirms the location of Gc in the density spanning from the membrane-distal globular lobes to the viral membrane, as we and others have proposed previously ( Li et al, 2016 ; Serris et al, 2020 ). The fitting locates domain III of the Gc adjacent to the membrane, allowing the transmembrane region of the C-terminus to be linked to the virion envelope ( Figures 5A and 2A ), and places the fusion loop from Gc domain II into membrane-distal lobe density in close contact with Gn ( Figure 5A and B ), in a manner similar to that observed for other class II fusion proteins and their cognate accessory proteins ( Halldorsson et al, 2018 ; Voss et al, 2010 ).…”
Section: Resultssupporting
confidence: 91%
“…Cryo-ET of purified PUUV VLPs, in tandem with sub-tomogram averaging, revealed that the VLP surface displays the expected Gn−Gc spike architecture that can form locally ordered lattices, as observed in native hantavirions ( Figure 4—figure supplement 1 ). Consistent with previous studies of hantavirus ultrastructure and Gc oligomerization ( Bignon et al, 2019 ; Li et al, 2016 ), breakpoints exist in the (Gn−Gc) 4 lattices ( Huiskonen et al, 2010 ; Li et al, 2016 ; Serris et al, 2020 ). Previous studies have suggested that contacts between (Gn−Gc) 4 spikes are mediated by Gc homo-dimers ( Bignon et al, 2019 ; Huiskonen et al, 2010 ; Li et al, 2016 ), while lattice breaks are expected to display Gc (‘lattice-free Gc’) molecules that are not integrated within the lattice assembly through Gc homo-dimer interactions.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations